2011
DOI: 10.1039/c0jm03337e
|View full text |Cite
|
Sign up to set email alerts
|

A new application of mesoporous carbon microparticles to nucleic acid detection

Abstract: Mesoporous carbon (MC) materials are important in many areas of technology, such as in storage of hydrogen and methane, supercapacitors, molecular separation, catalysis, etc. In this communication, we demonstrate the proof of concept of using MC microparticles as an effective fluorescent sensing platform for nucleic acid detection with a high selectivity down to single-base mismatch.During recent years, the detection of nucleic acid has been paid much attention due to their various applications in gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 22 publications
(12 reference statements)
0
38
0
Order By: Relevance
“…carbon nanotubes and graphene oxide). [20][21][22][23][24][25][26] Graphene is a single layer of graphite with many superior electronic and mechanical properties. [27][28][29][30] By generating surface hydroxyl and carboxyl groups, the resulting graphene oxide (GO) can disperse in water.…”
Section: Introductionmentioning
confidence: 99%
“…carbon nanotubes and graphene oxide). [20][21][22][23][24][25][26] Graphene is a single layer of graphite with many superior electronic and mechanical properties. [27][28][29][30] By generating surface hydroxyl and carboxyl groups, the resulting graphene oxide (GO) can disperse in water.…”
Section: Introductionmentioning
confidence: 99%
“…(2012 Submitted to -2 -process, the fluorophore-to-GO distance increased from zero to infinity to achieve the maximal fluorescence enhancement. In addition to GO, many other carbon based nanomaterials including carbon nanotubes, [25][26][27][28][29] mesoporous carbon, [30] carbon nanoparticles [31,32] and water soluble nano-C60 [33] have also been tested for similar applications.On the other hand, little is known about DNA length-dependent fluorescence quenching within a few nanometers from the GO surface. Such information is important for rational design of covalently linked probes.…”
mentioning
confidence: 99%
“…It is also of importance to note that the use of 12 L MCMPs can give a maximal fluorescence quenching efficiency and thus an optimal volume of 12 L was chosen in our present study. When TA molecules are mixed with MCMPs, TA will adsorb on the microparticles surface due to -stacking effects of DNA bases on -rich MCMP (Varghese et al, 2009;Liu et al, 2011) leading to substantial quenching of dye fluorescence due to their very close proximity (McCreey, 2008;Yang et al, 2004). We have found that the adding of MCMPs into fluorescein solution only leads to slight decrease of the fluorescence of fluorescein in intensity (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…The mesoporous nature of these microparticles was confirmed by the corresponding XRD and nitrogen adsorption-desorption isotherm analysis. These MCMPs have uniform pore structure and narrow pore size distribution around 4.0 nm (Liu et al, 2011). The performance of this MCMP-based aptasensor for TB detection was studied in the following fluorescence experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation